2022
DOI: 10.1088/2053-1591/ac73e2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing temperature on structural phase transition and microstructure evolution of hydrothermally synthesized barium titanate nanoparticles

Abstract: Commercial hydrothermally synthesized BaTiO3 powder with a cubic structure was annealed in a temperature range of 650–900 ℃, and the cubic-tetragonal structure transition and microstructure evolution of the powder were investigated in relation to the annealing process. The BaTiO3 powder used had a cubic structure below an annealing temperature of 800 ℃ and a tetragonal structure above 850 ℃. Particle growth occurred under a low activation energy of ~33.2 kJ/mol because of the nanocrystalline size effect, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The hydrothermally synthesized BaTiO3 nanopowders with a mean particle size of ∼100 nm, purity of 99.95%, and cubic crystal structure (Shandong Sinocera Functional Material Co., Ltd, China) were synthesize and annealed at 600 °C and 750 °C for 5 h to increase the particle size without transforming the crystal structure from cubic to tetragonal, which is based on empirical research that the phase transition of hydrothermally synthesized BaTiO 3 occurs at annealing temperatures higher than 850 °C [16]. Three powders with different particle sizes were prepared by the annealing process and compressed into a cylindrical shape with a diameter of 6 mm and thickness of 2 mm at 60 MPa for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrothermally synthesized BaTiO3 nanopowders with a mean particle size of ∼100 nm, purity of 99.95%, and cubic crystal structure (Shandong Sinocera Functional Material Co., Ltd, China) were synthesize and annealed at 600 °C and 750 °C for 5 h to increase the particle size without transforming the crystal structure from cubic to tetragonal, which is based on empirical research that the phase transition of hydrothermally synthesized BaTiO 3 occurs at annealing temperatures higher than 850 °C [16]. Three powders with different particle sizes were prepared by the annealing process and compressed into a cylindrical shape with a diameter of 6 mm and thickness of 2 mm at 60 MPa for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Barium hydroxide is present as barium ions, whereas titania exists as a solid phase that dissolves into the liquid phase to participate in the reaction of equation (1). The hydrothermally synthesized BaTiO 3 powders initially contain H 2 O and OH − , which are eliminated by an annealing process that transforms the crystalline structure from cubic to tetragonal [16]. Notably, the hydrothermal technology has also been used to synthesize BaTiO 3 single crystals and thin films [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of tetragonal distortion of BT (tetragonality, the ratio of the lattice parameter c to a) caused by the eccentric displacement of titanium atoms is commonly used Materials 2023, 16, 4191 2 of 12 to measure the dielectric properties [13,14]. The higher the ratio of c/a, the higher the dielectric constant of the BT powder [15].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a high c/a ratio and suitable particle size are essential to obtain high-performance BT powders. The crystal structure and dielectric properties of BTPs are also affected by their shape, size, and uniformity [16]. Nevertheless, previous studies have shown that the structure of BT powders obtained by traditional hydrothermal methods generally presents the cubic phase or a small amount of tetragonal phase, which is unfavorable for the dielectric properties [17,18].…”
Section: Introductionmentioning
confidence: 99%